Methodological Principles of Analysis Pertaining to Running Repair Switchings-off of Main Equipment of Power System - O. I. Aleksandrov; M. M. Norejko; A. M. Norejko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers methodological principles of optimum planning of running repair switchings-off of power system equipment. Strategy concerning the decision of the problem under modern operational conditions and influential factors are given and determined in the paper. The paper also considers some peculiar features of the requirements which are to be formalized on the basis of informational technologies.